2005
DOI: 10.3390/s5010070
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin Modified Electrode Surface as a Sensitive Heavy- Metal Ion Biosensor

Abstract: Electrochemical biosensors have superior properties over other existing measurement systems because they can provide rapid, simple and low-cost on-field determination of many biological active species and a number of dangerous pollutants. In our work, we suggested a new heavy metal biosensor based on interaction of heavy metal ions (Cd 2+ and Zn 2+ ) with phytochelatin, which was adsorbed on the surface of the hanging mercury drop electrode, using adsorptive transfer stripping differential pulse voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 88 publications
(64 reference statements)
0
26
0
1
Order By: Relevance
“…In addition the limit quantification of apoMT was 100 pM at t A 500 s. Moreover, apoMT has been successfully used for suggestion of EDTA MT biosensor for determination of heavy metals [65]. We found out that the suggested biosensor had similar behavior as MT and/or PC biosensor, whereas the biological part of EDTA MT biosensor enabled to reach lower detection limits about 10 -30% [34,55].…”
Section: Electroanalytical Determination Of Apomtmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition the limit quantification of apoMT was 100 pM at t A 500 s. Moreover, apoMT has been successfully used for suggestion of EDTA MT biosensor for determination of heavy metals [65]. We found out that the suggested biosensor had similar behavior as MT and/or PC biosensor, whereas the biological part of EDTA MT biosensor enabled to reach lower detection limits about 10 -30% [34,55].…”
Section: Electroanalytical Determination Of Apomtmentioning
confidence: 77%
“…A few authors shown in Table 1 have used sodium chloride (0.5 M, pH 6.4) as a supporting electrolyte that has similar pH and ionic strength as physiological environment [34,55,56]. We again picked up the threads of a previous work and observed influence of changes of supporting electrolyte pH (0.5 M NaCl) within the range from 6.0 to 7.6 (adjusted by additions of HCl and/or NaOH) on electrochemical signal of MT.…”
Section: Influence Of a Supporting Electrolyte And Its Ph On Electrocmentioning
confidence: 99%
“…Moreover, this electrochemical technique has been intensively used for the study of electrochemical metallothionein behaviour too [27][28][29]58,59]. On the base of the abovementioned results with reducing agent (TCEP), we primarily studied the effect of the TCEP on AdTS DPV signals of In our previous experiments, we proved that free ions of heavy metals are not able to be adsorbed which makes detection of the free ions impossible [52,60].…”
Section: Differential Pulse Voltammetrymentioning
confidence: 95%
“…Until the SH-SAMMS ™ -Nafion sensors, this low concentration range of metal ions in un-pretreated natural waters has been extremely difficult to detect using mercury-free electrodes. Although others have reported the detection limits of Cd, Pb, and Cu to be in low ppb levels at either mercury based electrodes or mercury-free electrodes, the values were based on 3S/N and were measured in metal spiked buffered solutions rather than in real samples [40][41][42][43]. Simultaneous detection of Cd, Pb, and Cu in 0.01 M CH 3 COONa after 3 minutes of preconcentration in a very low concentration range (0 to 10 ppb), relevant to trace level assay of the metal ions was also demonstrated in Figure 6.…”
Section: Detection Of Pb CD and Cumentioning
confidence: 99%